Consumer Protection and Legal Uncertainty in Ride-Hailing Pick-Up Practices in Bandung - Difa Kusumadewi; Ridwan Sutriadi; Sonny Yuliar; Ibnu Syabri (UIN Sunan Gunung Djati, 2026)
Consumer protection challenges in ride-hailing services emerge during the pick-up stage, where passengers are exposed to spatial uncertainty, unsafe waiting environments, and unclear accountability among platforms, drivers, and local authorities. Although ride-hailing services have been formally legalized in Indonesia, legal recognition alone does not automatically ensure consumer protection during the pick-up stage, particularly in relation to passenger safety, spatial certainty, and legal accountability. Passengers are frequently directed to informal, prohibited, or potentially unsafe public spaces, raising concerns regarding safety, legal responsibility, and the right to clear and reliable service information. To address these concerns, this research examines how transportation regulations, platform systems, and spatial conditions shape ride-hailing pick-up practices in Bandung, Indonesia. Using a qualitative case study approach, this study combines regulatory analysis, field observations, and in-depth interview with drivers and passengers. The analysis was guided by the Staging Mobilities framework and material semiotics approach to understand how mobility practices are negotiated in everyday urban settings. The findings then show that the drivers and passengers continuously negotiate pick-up locations by adapting to traffic conditions, spatial constraints, and platform instructions. They often prioritizing practicality and accessibility over formal compliance. These negotiations frequently occur in legally ambiguous situations and potentially unsafe spaces, including roadside and no stopping areas. The findings indicate that consumers already rely on platforms before the ride formally begins, yet legal accountability for passenger safety among platforms, drivers, and local authorities remains unclear.